(untitled) - Ashihara, Yoshinobu (New York, 1989)
The book consists of the following four parts such as: a new appraisal of the Tokyo townscape, the view within, the hidden order, and Tokyo a city apart.
Keywords: Architecture; 20th century; Tokyo, Japan